Electrotechnologies applied to microalgal biotechnology – Applications, techniques and future trends. (October 2018) - Geada, Pedro; Rodrigues, Rui; Loureiro, Luís; Pereira, Ricardo; Fernandes, Bruno; Teixeira, José A.; Vasconcelos, Vítor; Vicente, António A.
Abstract: Electrotechnologies are based on the direct application of an external electric field through a given semi-conductive material. These technologies are part of a wide range of biotechnological processes, considered cost-effective and environmentally-friendly in view of the less intensive use of non-renewable resources and high levels of energetic efficiency. In this regard, electrotechnologies are a promising processing tool to overcome some of the microalgae's exploitation limitations. The application of electric field-based techniques can cover upstream (i.e. electroporation for genetic transformation, inactivation of culture contaminants, and improvement of growth kinetics) and downstream processes (e.g. harvesting and extraction methods). Pulsed electric fields (PEF) and moderate electric fields (MEF), targeted at microalgae cellular permeabilization and subsequent extraction of valuable compounds, count with a substantial body of fundamental research which puts them on the front row to become mainstream techniques in a near future. This review provides comprehensive knowledge systematization of the current status of the direct application of these techniques on microalgal biotechnology, as wells as future trends and challenges regarding developments in electrotechnologies to be applied to microalgae industrial exploitation. Highlights: The potential and limitations in microalgae biotechnology are addressed. Applications and perspectives of electrotechnologies are discussed. Electrotechnologies can have a transversal impact in microalgae biotechnology. Electrotechnologies can drive microalgae production towards a biorefinery approach.